DAMANG JAYA (MANGO LEAVES AND PAPAYA SEEDS): ERADICATION AGENT OF ASCARIASIS - Andi Radiah Permatasari (Hasanuddin University, 2018)
ascaria Lumbricoides has become a long-standing world problem with WHO 2015 prevalence of approximately 24% of the world's population or about 1.5 billion people and about 28% of Indonesia's population according to kemenkes 2015. In urban communities, ascariasis is overcome through anthelmintic drugs believed to cause the receptivity of the drug against worms Ascariasis sp. Therefore, the research of mango leaf and papaya seeds infusion aims to produce natural antihelmintic substances that are easy to find both in the city and in the interior though. This study used pure experimental design (True Experimental) in vitro using 4 treatment groups. Control group (P0) was given Nacl as a negative control, treatment group 1 (P1) was given mango leaf infusion, treatment group 2 (P2) was given papaya seed infusion, and treatment group 3 (P3) was given mango and papaya seed infusa. In the treatment of infusa given as much as 100 ml per petri dish In this study the animal try is diguanakan chicken. The results obtained in this study is found the youngest worms die on papaya seed infusa, then infusa mango leaves and papaya seeds and the last mango leaves infusa.